Perlaksanaan amalan pengilangan baik (APB) dalam kawalan kualiti dan keselamatan kosmetik di Utara Malaysia - Nur Faizah, Azali (2022)
The continuous development and evolution of the cosmetics industry have opened up opportunities for founders to market various types of self-branded cosmetic products, through contract manufacturing services, eventhough with where they require less experience and knowledge related to cosmetics products and only required a small capital. This situation has led to the dumping of cosmetic products in the market with dubious quality and safety status. In fact, the entire responsibility for complying with the rules of safety and quality of cosmetic products rests entirely with the manufacturer or supplier (founder). Therefore, this study was conducted to analyse the issues related to product quality and safety among cosmetics founders in North Malaysia, towards implementing Good Manufacturing Practices (GMP), and comply with the established standard. The study used observation methods and questionnaires distributed to cosmetics founders in the northern region of Malaysia because it has a high number of cosmetic manufacturers. The findings indicate that the variables of material content, training and documentation, as elements in Good Manufacturing Practices moderated by Supply Chain Management, have positive and significant interactions with the performance of cosmetic products. The findings of this study are beneficial and can help cosmetics founders understand the need to comply with these cosmetic control standards as a basic requirement in the production of quality and safe cosmetics while helping consumers realize the effects of using substandard and risky cosmetics. There is a high need for mandatory compliance to standards for manufactures (founders) for ensure the quality and safety of cosmetics in Malaysia.